Moon Girl and Devil Dinosaur. Vol. 3, The smartest there is! - Montclare, Brandon; Reeder, Amy, 1980- (Marvel Worldwide, Inc., 2017)
"Tony Stark,T'Challa, Amadeus Cho...the greatest minds in the Marvel Universe all have one thing in common: they're not smarter than a 4th grader! Now it's time to put Lunella's unrivaled intellect to the test against some of Marvel's finest-- with Devil Dinosaur adding the brawn to her brains. The Thing stops in to defend his missing best pal Reed Richards' pole position!" -- page 4 of cover.